2020
DOI: 10.1017/s0950268820002630
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with morbidity and mortality outcomes of COVID-19 patients on the 28th day of the disease course: a retrospective cohort study in Bangladesh

Abstract: Diverse risk factors intercede the outcomes of coronavirus disease 2019 (COVID-19). We conducted this retrospective cohort study with a cohort of 1016 COVID-19 patients diagnosed in May 2020 to identify the risk factors associated with morbidity and mortality outcomes. Data were collected by telephone-interview and reviewing records using a questionnaire and checklist. The study identified morbidity and mortality risk factors on the 28th day of the disease course. The majority of the patients were male (64.1%)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 13 publications
3
43
3
Order By: Relevance
“…By occupation, nearly half of the patients were service holders. In this respect, the study conducted by Islam MZ et al [1] also found the majority of the patients as service holders but it was relatively lower (32.5%) than the current study. It could be justified by the reality that a remarkable segment of the people of Bangladesh are involved in diverse private and public jobs for their survival, and they have to move outside to attend their job stations.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…By occupation, nearly half of the patients were service holders. In this respect, the study conducted by Islam MZ et al [1] also found the majority of the patients as service holders but it was relatively lower (32.5%) than the current study. It could be justified by the reality that a remarkable segment of the people of Bangladesh are involved in diverse private and public jobs for their survival, and they have to move outside to attend their job stations.…”
Section: Discussioncontrasting
confidence: 73%
“…Around half of the COVID-19 patients were young adults (age group 30-49 years) and only 11.0% of the patients were elderly (age group 60-90 years). The demographic profile of Bangladesh depicts that 40.07% of the population belongs to the age group of 25–54 years and only 6.42% belongs to the age group >60 years [1]. In this regard, it could be claimed that the age distribution of the patients is in alignment with the national age distribution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study also portrayed that more than one-third (35.5%) of the COVID-19 patients had different comorbidities including hypertension, diabetes mellitus, ischaemic heart disease, chronic lung, kidney, and liver diseases. The former study conducted by Islam MZ et al [1] also identi ed nearly the same proportion (33.9%) of the COVID-19 patients having comorbidities including hypertension, coronary heart disease, diabetes mellitus, cancers, chronic lung, kidney, and lier diseases. The comorbid patients were at higher risk of worse morbidity and mortality consequences of COVID-19, and they were referred to health facilities to exclude COVID-19.…”
Section: Discussionmentioning
confidence: 73%